How to perceive the corporate social responsibility in the agro-food companies? - Ubreziova, Iveta; Moravcikova, Kamila (Serbian Journal of Management, 2017)
The basic aim of the article is to evaluate the extent of a companies´ engagement with CSR as well as to uncover the nature and type of CSR activities in the agro-food companies operating in the Slovak Republic. In order to fulfill the basic aim, we set the partial aims which involve several research questions. Primary information and data were obtained by the questionnaire survey in order to assess the level of companies´ engagement with CSR policy and activities they carry out within this policy. Secondary data consist of various publications, web-pages of selected companies, their annual general statements and statements concerning CSR policy. To every company, one questionnaire was distributed – in some case, it was possible to send it directly to person responsible for CSR activities. To graphically display our results, we used MS Excel and for other statistical processing SAS and SPSS. According to the results and findings from the questionnaire survey, the authors of the article finds it appropriate to offer several recommendations and ideas dealing with support of CSR in the Slovak Republic.
Keywords: SOCIAL RESPONSIBILITY; questionnaires; policy; activity; company; CSR